Cryptosporidiosis in Southeast Asia: what's out there? - Lim, Y. A. L.; Jex, A. R.; Smith, H. V.; Gasser, R. B. (Elsevier, 2010)
Cryptosporidiosis is a socioeconomically important, enteric disease caused by a group of protozoan parasites of the genus Cryptosporidium. The significant morbidity and mortality in animals and humans caused by this disease as well as its considerable impact on the water industry have made its prevention and control a global challenge, particularly given that there are presently no widespread, affordable or effective treatment or vaccination strategies. Although much is known about Cryptosporidium and the impact of cryptosporidiosis and other diarrhoeal diseases in developed countries, this is not the case for many developing countries in Africa, South America and Asia. In Southeast Asia, which represents an epicentre for emerging infectious diseases, cryptosporidiosis has been reported in countries, such as Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand and Vietnam. In most of these countries, the likely predisposing factors for cryptosporidiosis include rapid population growth and expanding urbanisation (which are often linked to inadequate municipal water supplies and poorly managed refuse disposal) as well as the tropical climate and the increasing prevalence of HIV/AIDS and other infectious diseases. Given the close proximity of these countries and the extent of migration within and among them, cryptosporidiosis can be difficult to control. National and regional surveillance is central to preventing and controlling cryptosporidiosis. To date, most studies of cryptosporidiosis in Southeast Asia have focus on estimating the prevalence of infection in humans and animals using conventional diagnostic techniques. Future investigations using reliable molecular tools should enable improved insights into the epidemiology, systematics and population genetics of Cryptosporidium in this region. An enhanced understanding of the transmission of cryptosporidial infections and the significance of environmental contamination will require a multidisciplinary approach, built on shared resources. Such an integrated approach would underpin stable and powerful partnerships in efforts to prevent and control this disease. The purpose of the present chapter is to review available data and information on cryptosporidiosis in Southeast Asia and to provide recommendations in the pursuit of a better understanding of Cryptosporidium in this region, in order to facilitate the development of effective multidisciplinary interventions to control cryptosporidiosis.